Collaborative Governance In The Implementation Of The West Semarang Drinking Water Management System (SPAM) - Hilmie, Farkhan; Larasati, Endang; Dwimawanti, Ida Hayu; Yuwono, Teguh (Jurnal Mamangan, 2023)
Drinking water is a vital human need that must be met. Meeting the needs of drinking water is a right for everyone. Drinking water management system infrastructure is a homework that has not been fulfilled optimally. Various problems become obstacles in meeting the target of universality of drinking water services for everyone. This has resulted in the low achievement of drinking water services in Indonesia. This article analyzes the collaboration process in providing a drinking water management system through the Government and Business Entity Cooperation (PPP) scheme of the West Semarang Drinking Water Management System (SPAM), Semarang city with Anshel and Gash collaboration process theory. The writing of this article uses a qualitative approach with a descriptive type of research. The collaborative governance process in every stage runs well. Involvement between actors in accordance with the competence of their respective roles so as to accelerate the collaboration process. Successful collaboration processes need to be implemented in other regions to accelerate the achievement of sustainable developments goals water and sanitation targets..